Recent Advances in High‐Mobility and High‐Stretchability Organic Field‐Effect Transistors: From Materials, Devices to Applications. Issue 12 (22nd October 2021) - Wu, Fuming; Liu, Yixuan; Zhang, Jun; Duan, Shuming; Ji, Deyang; Yang, Hui
Abstract: Stretchable organic field‐effect transistors (OFETs) are one of the essential building blocks for next‐generation wearable electronics due to the high stretchability of OFET well matching with the large deformation of human skin. In recent years, some significant progress of stretchable OFETs have already been made via the strategies of stretchable molecular design and geometry engineering. However, the main opportunity and challenge of stretchable OFETs is still to simultaneously improve their stretchability and mobility. This review covers the recent advances in the research of stretchable OFETs with high mobility. First, the core stretchable materials are summarized, including organic semiconductors, electrodes, dielectrics, and substrates. Second, the materials and healing mechanism of self‐healing OFET are summarized in detail. Subsequently, their different configurations and the potential applications are summarized. Finally, an outlook of future research directions and challenges in this area is presented. Abstract : The application of stretchable organic field‐effect transistors (OFETs) in wearable devices has attracted widespread attention. Achieving high mobility and high stretchability remains the most important challenge for stretchable OFETs. In this review, the core materials, structure, and fabrication strategies of the device, as well as the related applications are systematically introduced. Finally, existing challenges and future directions are proposed.